A Cost Analysis of Internal Fixation Versus Nonoperative Treatment in Adult Midshaft Clavicle Fractures Using Multiple Randomized Controlled Trials. Issue 4 (April 2015) - Walton, Blaine; Meijer, Karim; Melancon, Keith; Hartman, Michael
Abstract : Background: To determine whether the cost of nonoperative treatment, including those who require delayed operative treatment, is less than those receiving initial operative management. Methods: We identified 4 recent randomized controlled trials comparing operative and nonoperative treatment of displaced midshaft clavicle fractures in adults with a minimum of 1-year follow-up. A decision tree was then created from these data using reoperation for those treated with surgery or delayed operative treatment of those treated nonoperatively as end points. Actual costs estimated from 2013 Medicare reimbursement rates were applied and adjusted to better reflect private insurance rates. We then performed a 2-way sensitivity analysis to test the stability of our model. Results: Based on our decision tree, the expected costs for operative and nonoperative treatment were $14, 763.21 and $3112.65, respectively, producing a cost savings of $11, 650.56 with nonoperative treatment. After application of a 2-way sensitivity analysis, our model remains valid until delayed operative treatment for nonoperative patients approaches 95% and reoperation after initial operative management falls below 15%. Conclusions: From the perspective of a single payer, initial nonoperative treatment of midshaft clavicle fractures followed by delayed surgery as needed is less costly than initial operative fixation. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence.